2007
DOI: 10.1074/jbc.m605064200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Induces MafA Expression in Pancreatic Beta Cell Lines via the Hexosamine Biosynthetic Pathway

Abstract: MafA is a basic leucine zipper transcription factor that regulates gene expression in both the neuroretina and pancreas. Within the pancreas, MafA is exclusively expressed in the beta cells and is involved in insulin gene transcription, insulin secretion, and beta cell survival. The expression of the mafA gene within beta cells is known to increase in response to high glucose levels by an unknown mechanism. In this study, we demonstrate that pyruvate, which is produced by glycolysis from glucose, is not suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 75 publications
0
60
0
1
Order By: Relevance
“…It is in large part regulated by the flux of glucose through the HBP and generation of UDP-GlcNAc, which in β-cells is proportional to the extracellular glucose concentration (30). In β-cells O-GlcNAcylation mediate the induction of MafA expression by glucose (21) and the subcellular distribution of BETA2 (31). Here, we show that glucose increases O-GlcNAcylation of Pdx-1, but not BETA2, in the nucleus and its recruitment to the GPR40 promoter.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is in large part regulated by the flux of glucose through the HBP and generation of UDP-GlcNAc, which in β-cells is proportional to the extracellular glucose concentration (30). In β-cells O-GlcNAcylation mediate the induction of MafA expression by glucose (21) and the subcellular distribution of BETA2 (31). Here, we show that glucose increases O-GlcNAcylation of Pdx-1, but not BETA2, in the nucleus and its recruitment to the GPR40 promoter.…”
Section: Discussionmentioning
confidence: 81%
“…4A). Alternatively, glucose can induce gene transcription via its metabolism through the hexosamine biosynthesis pathway (HBP) (20)(21)(22)(23). To determine the contribution of the HBP to the induction of GPR40 mRNA by glucose, we measured GPR40 mRNA levels in islets treated with the HBP intermediate N-acetyl glucosamine (GlcNAc; 20 mmol/L), which promotes OGlcNAc modification of proteins (also known as O-GlcNAcylation) by increasing UDP-GlcNAc (24).…”
Section: Glucose Stimulation Of Gpr40 Expression Is Mediated By Thementioning
confidence: 99%
“…In mice lacking MafA, reduced insulin 1 and 2 gene transcription, glucose intolerance and development of diabetes mellitus was observed [12]. At least at the beta cell level the transcriptional activity of MafA seems to be regulated by either changes in MafA synthesis or by an enhanced degradation of this protein [11,16,26,48,49]. However, in the present study overproduction of MEKK1 did not decrease the amount of MafA produced in JEG cells (data not shown), arguing against a MEKK1-induced degradation of MafA.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism by which phosphorylated MafA undergoes rapid degradation in response to low glucose is still unknown. Recently, Vanderford et al showed that MafA induction by glucose is mediated by hexosamine biosynthetic pathway [42]. Therefore, O-GlcNAc modification of MafA and/or proteasome subunits may be involved in the regulation of MafA protein abundance.…”
Section: Maf Transcription Factors As Regulators Of Tissue-specific Gmentioning
confidence: 99%